Aggregation Behavior of Task‐Specific Acidic Ionic Liquid N‐Methyl‐2‐Pyrrolidinium Dihydrogen Phosphate [NMP][H2PO4] in Aqueous and Aqueous Salt Solutions - Pal, Amalendu; Saini, Mohit (Journal of surfactants and detergents, 2019)
The effect of alkali salt (NaCl, NaBr, and KCl) addition on aggregate formation of N‐methyl‐2‐pyrrolidinium dihydrogen phosphate [NMP][H2PO4] ionic liquid in aqueous solution was determined using surface tension at 298.15K and conductance from 288.15 to 308.15K. The surface parameters such as critical aggregation concentration (CAC), adsorption efficiency, surface pressure, surface tension at CAC, minimum surface cover by a single molecule, and maximum area excess concentration were calculated from surface tension measurements with and without salts. The results show that [NMP][H2PO4] forms aggregates at lower concentrations and is more surface active than classical cationic surfactants.